Satellite-to-ground radiowave propagation - Allnutt, J. E. (Jeremy E.) (London, United Kingdom The Institution of Engineering and Technology, 2011)
The book is divided into eight chapters: radiowave Earth-space communications; ionospheric effects; clear-air effects; attenuation effects; depolarization effects; mobile satellite service propagation effects; optical communications propagation effects; and restoration of performance during signal impairments.
Electronic reproduction.
Keywords: Radio wave propagation; Artificial satellites in telecommunication; Ionospheric radio wave propagation; Optical communications; Radio wave propagation; Telecommunication -- Equipment and supplies; Electronic books